PjBL Learning Model Assisted by YouTube: The Effect on Student’s Critical Thinking Skills and Self-Confidence in Physics Learning - Fadilah, Siti; Yuberti, Yuberti; Hidayah, Nurul (CV FOUNDAE, 2023)
Low critical thinking skills and self-confidence can affect the learning process of students. In overcoming this problem, a suitable learning model and learning media are needed. This study aims to determine the effect of the YouTube-assisted PjBL learning model on students' critical thinking skills and self-confidence. This research is quasi-experimental with a non-equivalent control group design. The population in the study consisted of 185 eleventh-grade students of SMAN 16 Bandar Lampung. The research sample consisted of classes, class XI IPA 1 as the control class and XI IPA 2 as the experimental class, selected by cluster random sampling technique. Data collection instruments were an essay test of five questions and self-confidence questionnaires. Based on the analysis using the MANOVA test, the significant values for critical thinking skills of 0.008 and self-confidence of 0.000 were obtained. These values indicate that Â is accepted. Thus, it can be concluded that the YouTube-assisted PjBL learning model affects students' critical thinking skills and self-confidence in physics learning.